Business Philosophy: Modern Trends and Digital Solutions - Baurina, Svetlana; Pashkovskaya, Margatita; Nazarova, Elena (Տիգրան Մեծ)
This article focuses on the modern vision of business philosophy. The authors of the article correctly substantiated the significance and extreme need to use philosophical knowledge and thinking both during the initiation and implementation of entrepreneurial ideas and during the practical implementation of entrepreneurial activity and direct business. Modern realities give the businessman the opportunity for independent choice, and a professional approach in business conductis essential. The philosophical thinking of the entrepreneur, according to the authors, is the way to efficient business. Mastering the philosophy of business and the practical use of its provisions will ensure sustainable long-term success in the entrepreneurial environment. The realities of pervasive digitalization can fill with new semantic content modern processes in business with the parallel natural development of morality and culture. The new digital ecosystem is designed to combine the brilliant potential of the machine with an unsurpassed human mind to introduce technological innovations in business structures at the most favourable level.
Keywords: Philosophy of economics